Healthwashing in high-sugar food advertising: the effect of prior information on healthwashing perceptions in Austria. - Heiss, Raffael; Naderer, Brigitte; Matthes, Joerg (Health promotion international, 2021)
In the context of exceeding levels of sugar consumption, some food companies advertise high-sugar products using inappropriate and misleading health claims (i.e. healthwashing). To reduce sugar consumption, consumers need to recognize what these healthwashed claims are. This study investigates how prior sugar-related health information moderates the effect of exposure to healthwashed advertisements (ads) on healthwashing perceptions and how such perceptions are related to attitudes towards product consumption. We conducted a 2 × 2 online experiment with 292 adult participants in Austria. We manipulated the presence of healthwashing and participants' prior sugar-related health information. The results indicated that exposure to healthwashed ads increased healthwashing perceptions only when the participants received additional health information prior to ad exposure, whereas no significant effect was found when the participants did not receive such prior health information. Healthwashing perceptions were then negatively related to individuals' attitudes towards product consumption. Based on these results, the study suggests that public access to health-related information might play an important role in empowering consumers to detect inappropriate health claims and become more critical towards food companies' underlying strategies in ads.
EVALuna2:523301